Reforming civil-military relations in new democracies : democratic control and military effectiveness in comparative perspectives - Croissant, Aurel; Kuehn, David (Springer, 2020)
Contents: Acknowledgments; Contents; Editors and Contributors; Chapter 1: Introduction; 1.1 Basic Concepts; 1.1.1 New Democracies; 1.1.2 Civil-Military Relations and Civilian Control; 1.1.3 Military Effectiveness; 1.2 Theoretical Perspectives and Themes; 1.3 The Contributions to This Volume; References; Chapter 2: The Long Shadow of History: Civilian Control and Military Effectiveness in Poland; 2.1 Introduction; 2.2 Historical Background; 2.3 Civilian Control of the Armed Forces: A Work in Progress; 2.4 Civilian Oversight and the Effectiveness of the Armed Forces; 2.5 Summary; References Contents: 4.3.2.2 Oversight4.3.2.3 Professional Military Education; 4.3.3 Effectiveness; 4.3.3.1 Strategy; 4.3.3.2 Chief of the General Staff of the Armed Forces (CEMGFA); 4.3.3.3 Resources; 4.4 Brazil; 4.4.1 Control; 4.4.1.1 Ministry of Defense (MOD); 4.4.1.2 Oversight: Public Ministry; 4.4.1.3 Professional Military Education; 4.4.2 Effectiveness; 4.4.2.1 Strategy; 4.4.2.2 Institutions; 4.4.2.3 Resources; 4.5 Explaining the Differences; 4.5.1 Portugal; 4.5.2 Brazil; 4.6 Conclusions; References; Chapter 5: Mexico: A Civil-Military ``Pact ́́Unravelling?; 5.1 Introduction Contents: 5.2 Historical Development of Civil-Military Relations in Authoritarian Mexico5.2.1 Origins and Structures of Civilian Control in Post-Revolutionary Mexico; 5.2.2 Authoritarian Legacies of PRI Rule; 5.3 Civil-Military Relations Since the Start of the Transition in 1988; 5.3.1 The Transfer of Power to the PAN and the First Years of Democratic Civil-Military Relations; 5.3.2 The Crises of 2006 and the Military in the ``War on Drugs;́́ 5.3.3 International Factors: The Intensified U.S. ``War on Drugs;́́ 5.4 Changing Roles: The ``War on Drugs ́́and Military Effectiveness; 5.5 Conclusion Contents: Chapter 3: Institutional Failure and Civic Activism: The Potential for Democratic Control in Post-Maidan Ukraine3.1 Introduction; 3.2 Civilian Control in Independent Ukraine; 3.3 The Effectiveness of the Ukrainian Army; 3.4 Civil Society as a Security Actor; 3.5 Making Civilian Control Democratic; 3.6 Conclusions; References; Chapter 4: Civil-Military Relations in Two ``Third Wave ́́Democracies: The First and a Follower; 4.1 Introduction; 4.2 The Framework; 4.2.1 Control; 4.2.2 Effectiveness; 4.3 Portugal; 4.3.1 Initial Reforms in the Early 1980s; 4.3.2 Control; 4.3.2.1 Institutions